Regulating levels of the neuromodulator d‐serine in human brain: structural insight into pLG72 and d‐amino acid oxidase interaction. (5th August 2016) - Birolo, Leila; Sacchi, Silvia; Smaldone, Giovanni; Molla, Gianluca; Leo, Gabriella; Caldinelli, Laura; Pirone, Luciano; Eliometri, Patrick; Di Gaetano, Sonia; Orefice, Ida; Pedone, Emilia; Pucci, Piero; et al.
Abstract : The human flavoenzymed ‐amino acid oxidase (hDAAO) degrades the NMDA‐receptor modulatord ‐serine in the brain. Although hDAAO has been extensively characterized, little is known about its main modulator pLG72, a small protein encoded by the primate‐specific gene G72 that has been associated with schizophrenia susceptibility. pLG72 interacts with neosynthesized hDAAO, promoting its inactivation and degradation. In this work, we used low‐resolution techniques to characterize the surface topology of the hDAAO–pLG72 complex. By using limited proteolysis coupled to mass spectrometry, we could map the exposed regions in the two proteins after complex formation and highlighted an increased sensitivity to proteolysis of hDAAO in complex with pLG72. Cross‐linking experiments by using bis(sulfosuccinimidyl)suberate identified the single covalent bond between T182 in hDAAO and K62 in pLG72. In order to validate the designed mode of interaction, three pLG72 variants incrementally truncated at the C terminus, in addition to a form lacking the 71 N‐terminal residues, were produced. All variants were dimeric, folded, and interacted with hDAAO. The strongest decrease in affinity for hDAAO (as well as for the hydrophobic drug chlorpromazine) was apparent for the N‐terminally deleted pLG72 72–153 form, which lacked K62. On the other hand, eliminating the disordered C‐terminal tail yielded a more stable pLG72 protein, improved the binding to hDAAO, although giving lower enzyme inhibition. Elucidation of the mode of hDAAO–pLG72 interaction now makes it possible to design novel molecules that, by targeting the protein complex, can be therapeutically advantageous for diseases related to impairment ind ‐serine metabolism. Abstract : The human pLG72 protein interacts with neosynthesized enzymed ‐amino acid oxidase, whose main role in the brain is the degradation of the NMDA‐receptor modulatord ‐serine. An aberrantd ‐serine‐dependent NMDA‐receptor activation is involved in a variety of neurological diseases. In this work, we used low‐resolution techniques, limited proteolysis, and biochemical experiments to characterize the topology of thed ‐amino acid oxidase–pLG72 complex.